2022
DOI: 10.3390/pathogens11121542
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Epidemiology of Respiratory Pathogens in Children during the COVID-19 Pandemic

Abstract: Since the outbreak of the COVID-19 pandemic, a significant decrease in non-COVID-19 respiratory illnesses were observed, suggesting that the implementation of measures against COVID-19 affected the transmission of other respiratory pathogens. The aim of this study was to highlight the changes in the epidemiology of respiratory pathogens in children during the COVID-19 pandemic. All children with Severe Acute respiratory illness admitted to the pediatric departments between January 2018 and December 2021 with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
1
8
1
Order By: Relevance
“…In this study, HRSV infection notably increased in 2021 despite the circulating strains being closely related to those circulating in 2020 (Figure 1). This observation differs from other studies that reported a low level of HRSV infections during this same period but a large increase in HRSV cases during the summer and fall months in 2021 13–16 . The rapid resurgence of HRSV infections in 2021 was thought to be due in part to the reduced population‐level immunity, the largely relaxed NPIs, as well as the reopening of schools.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…In this study, HRSV infection notably increased in 2021 despite the circulating strains being closely related to those circulating in 2020 (Figure 1). This observation differs from other studies that reported a low level of HRSV infections during this same period but a large increase in HRSV cases during the summer and fall months in 2021 13–16 . The rapid resurgence of HRSV infections in 2021 was thought to be due in part to the reduced population‐level immunity, the largely relaxed NPIs, as well as the reopening of schools.…”
Section: Discussioncontrasting
confidence: 84%
“…This observation differs from other studies that reported a low level of HRSV infections during this same period but a large increase in HRSV cases during the summer and fall months in 2021. [13][14][15][16] The rapid resurgence of HRSV infections in 2021 was thought to be due in part to the reduced population-level immunity, the largely relaxed NPIs, as well as the reopening of schools. RV is one of the major causes of severe respiratory illnesses, competing with the burden of influenza and HRSV in terms of severity, economic cost, and resource utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, seasonal influenza deserves attention, and many researchers are concerned about the alternate epidemics of influenza and COVID‐19. During the COVID‐19 period, there was a severe lack of screening and detection for influenza A 57,58 . Besides, adverse events of the COVID‐19 vaccine, such as neurotoxic side effects, led to a decrease in people's willingness to vaccinate against the influenza vaccine 59–61 .…”
Section: Discussionmentioning
confidence: 99%
“…RSVneutralizing antibodies (nAb) were seen to be reduced in childbearing and breastfeeding women, increasing the number of children susceptible to RSV (7,(11)(12)(13). Interestingly, studies (11,(14)(15)(16)(17)(18)(19)(20) have reported low levels of RSV circulation following the outbreak of SARS-CoV-2, but also an out-of-season outbreak following the relaxation of public health measures, due to the accumulation of susceptible subjects. By contrast, a parallel increase in RSV infection in older adults was not observed, suggesting that behavioral changes implemented during the pandemic may have reduced RSV infection rates in this age-group (21).…”
Section: Introductionmentioning
confidence: 99%